Brain-wide mapping of developmental trajectories of cerebellar efferent projections - Raquel Murcia-Ramón; Martina Riva; Sergio Muñoz-Cobos; Ángeles Arzalluz-Luque; Juan Antonio Moreno-Bravo (Proceedings of the National Academy of Sciences, 2025)
Long-range cerebellar outputs are critical for shaping brain-wide functional architecture, influencing motor, cognitive, and affective domains. Proper cerebellar development and its efferent circuits are essential for brain maturation, and disruptions in these pathways have been implicated in neurodevelopmental disorders, such as autism spectrum disorder and schizophrenia. However, despite the early developmental onset, the spatiotemporal dynamics of cerebellar connectivity remain largely unknown, limiting mechanistic understanding of cerebellar contributions to brain development and disease. Here, we combine viral genetic tracing with high-resolution whole-brain 3D imaging to generate a comprehensive spatiotemporal map of cerebellar output development in mice. This systematic characterization uniquely distinguishes how excitatory and inhibitory cerebellar projections establish, expand, and refine their connectivity across the brain. Both axon types reach their principal brain targets within a narrow perinatal window, coinciding with the earliest formation of presynaptic terminals, and subsequently undergo postnatal expansion followed by region- and cell type–specific refinement. These findings define critical windows in the assembly of cerebellar output circuits, providing a framework to decipher the principles of cerebellar circuit formation and their impact on brain-wide function. Importantly, they also pinpoint periods of heightened vulnerability, when genetic or environmental perturbations are most likely to derail cerebellar-driven circuit maturation. By establishing this developmental blueprint, our study not only advances fundamental knowledge of brain wiring but also lays the groundwork for translational efforts to connect early cerebellar dysfunction with the origins of neurodevelopmental disorders.